2014
DOI: 10.1002/bsl.2133
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Static Factors Associated with Discharge Dispositions: The National Trajectory Project of Individuals Found Not Criminally Responsible on Account of Mental Disorder (NCRMD) in Canada

Abstract: The majority of individuals found not criminally responsible on account of mental disorder (NCRMD) in Canada spend some time in hospital before they are conditionally or absolutely (no conditions) discharged to the community by a legally mandated review board. By law, the decision to conditionally discharge an individual found NCRMD should be guided by the need to protect the public, the mental condition of the accused, and the other needs of the accused, especially regarding his/her community reintegration. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
76
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 53 publications
14
76
0
Order By: Relevance
“…Under a conditional discharge, the person returns to the community, but remains under the jurisdiction of the Review Board and is subject to specific conditions set by the Review Board. Examples of such conditions include residing in a specified place (e.g., supervised group home), refraining from using drugs and/or alcohol, following treatment recommendations, and travel restrictions (for more information, see Crocker, Nicholls, Charette, & Seto, ; Wilson et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under a conditional discharge, the person returns to the community, but remains under the jurisdiction of the Review Board and is subject to specific conditions set by the Review Board. Examples of such conditions include residing in a specified place (e.g., supervised group home), refraining from using drugs and/or alcohol, following treatment recommendations, and travel restrictions (for more information, see Crocker, Nicholls, Charette, & Seto, ; Wilson et al, ).…”
mentioning
confidence: 99%
“…To determine the appropriate disposition, the Review Board must rely on information that is presented for the hearing and conduct an individual assessment (s. 672.51, Criminal Code, ). Generally, the reports and the expert evidence provided to the Review Board offer information pertaining to the individual's mental and physical health, behavior, adherence to treatment/medication, and any notable events or behavior that occurred since the previous hearing (see Crocker et al, ; Wilson et al, ).…”
mentioning
confidence: 99%
“…For example, it was shown that the historical HCR-20 scale , living arrangement (Marshall et al, 2014;Novosad et al, 2014), financial resources, personality disorder, substance use disorder and number of incidents in the CR programme, were related to revocation of CR (Manguno-Mire et al, 2014). As highlighted by several scholars (Crocker et al, 2014;Gowensmith et al, 2014;Green et al, 2014;Manguno-Mire et al, 2014), more research into empirically validated CR related risk and protective factors is needed to provide the clinical and legal practice with an empirical basis to standardize the decision-making process into CR and to develop successful CR programmes. The HOM meso-measurements can provide for this much needed evidence based working model to research empirically validated factors to augment our empirical understanding of CR patients as to enhance CR risk assessment and management programmes.…”
Section: Meso-levelmentioning
confidence: 96%
“…This need to research different types of discharge by means of empirically supported methods to provide for a more efficient and effective treatment, is more readily stressed in a recent special issue of Behavioral Sciences and Law (32 (5), 2014) into the practices and outcomes of conditional release (CR) of criminal offenders with mental illness (Vitacco, Green & Felthous, 2014). To complement the lack of consensus in the clinical and legal practice of CR readiness risk assessment and management, these studies focused on (1) assessing risk and improving methodologies for evaluating CR readiness (Crocker, Nicholls, Charette & Seto, 2014;Douglas, 2014;Gowensmith, Bryant & Vitacco, 2014;Green et al, 2014) and (2) success and failure of CR (Manguno-Mire, Coffman, DeLand, Thompson & Myers, 2014;Marshall, Vitacco, Read & Harway, 2014;Novosad, Follansbee, Banfe & Bloom, 2014), to explore and validate empirically based CR related risk and protective factors for the development of standardized assessment protocols. Overall, these studies showed that a number of static and dynamic risk and protective factors were associated with failure and success of CR.…”
Section: Meso-levelmentioning
confidence: 98%
“…A major spark for this meeting was the reaction of the scientific community and of mental health and legal stakeholders when the Canadian federal government introduced the Not Criminally Responsible Reform Act (formerly introduced as Bill C-14 and C-54, 2013). Some elements of the Act, particularly the "high-risk" designation and dispositions, run counter to the scientific evidence on the trajectories of Canadian individuals found NCRMD (see papers from the National Trajectory Project, which are available at https://ntp-ptn.org in open access, as part of a special issue of Canadian Journal of Psychiatry: Charette et al, 2015;Crocker, Nicholls, Seto, Charette et al, 2015a;Crocker, Nicholls, Seto, Charette et al, 2015b;Nicholls et al, 2015; see also Crocker, Nicholls, Charette, & Seto, 2014;Salem et al, 2015;.…”
mentioning
confidence: 99%